Immunoproapoptotic molecule scFv-Fdt-tBid modified mesenchymal stem cells for prostate cancer dual-targeted therapy. (28th August 2017) - Yan, Fengqi; Li, Xia; Li, Nan; Zhang, Rui; Wang, Qinhao; Ru, Yi; Hao, Xiaoke; Ni, Jianxin; Wang, He; Wu, Guojun
Abstract: Highly efficient target therapy is urgently needed for prostate cancer with overexpression of γ-seminoprotein (γ-SM). Recent studies indicated that mesenchymal stem cells (MSCs) are attractive candidate for cell-based, targeted therapy due to their tumor tropism. Here we designed a dual-target therapeutic system in which MSCs were engineered to produce and deliver scFv-Fdt-tBid, a novel γ-SM-targeted immunoproapoptotic molecule. Such engineered MSCs (MSC.scFv-Fdt-tBid) would home to tumor sites and release the fusion protein to induce the apoptosis of prostate cancer cells. Our data demonstrated that scFv-Fdt-tBid showed a selective, potent and dose-dependent inhibition for γ-SM-positive cells (LNCaP, C4-2, 22Rv1) rather than γ-SM-negative cells and MSCs. Importantly, MSC.scFv-Fdt-tBid caused cell death through an apoptosis-dependent manner. Further, the tropism of MSC.scFv-Fdt-tBid to prostate cancer was verified both in vitro and in vivo . Finally, the in vivo experiments demonstrated that MSC.scFv-Fdt-tBid significantly inhibited γ-SM-positive tumor growth without toxic side effects. Collectively, this study represented a novel immunoproapoptotic molecule scFv-Fdt-tBid for γ-SM-positive tumors and demonstrated the therapeutic efficiency and safety of scFv-Fdt-tBid-modified MSCs against prostate cancers. Highlights: This study represented a novel immunoproapoptotic molecule scFv-Fdt-tBid. MSCs were engineered to produce and deliver scFv-Fdt-tBid. Designed a dual-target therapeutic system mediated by MSC.scFv-Fdt-tBid. Demonstrated the therapeutic efficiency and safety of MSC.scFv-Fdt-tBid.